tert-Butyl nitrite catalyzed synthesis of benzimidazoles from o-phenylenediamine and aldehydes at room temperature - Azeez S.; Sureshbabu P.; Chaudhary P.; Sabiah S.; Kandasamy J. (My University, 2025)
A simple and efficient method is demonstrated for the synthesis of benzimidazoles via cyclocondensation of o-phenylenediamine with aldehydes in the presence of catalytic amount of tert-butyl nitrite. All the reactions were carried out at room temperature while the desired products were obtained in good to excellent yields. © 2020 Elsevier Ltd